Bank Underwriting of Debt Securities: Modern Evidence - Gande, Amar; Puri, Manju; Saunders, Anthony; Walter, Ingo (Review of Financial Studies, 1997)
This article examines debt securities underwritten by Section 20 subsidiaries of bank holding companies relative to those underwritten by investment houses. Consistent with a net certification effect for banks, bank underwriting of lower credit rated firms to whom the bank lends results in relatively higher prices (lower yields). We find no evidence of conflicts of interest even when an issue is used to repay bank debt. Further, banks bring a relatively larger proportion of small issues to the market. Contrary to the contention that universal banking stunts availability of finance to small firms, bank underwritings appear to benefit small firms.